Alkali-Aggregate Reaction, AAR – Dealing with AAR in large concrete structures - Custódio, J. (2015)
A significant number of problems related to concrete deterioration have been detected in large concrete structures in Portugal and worldwide, the leading cause being AAR. The importance of these structures, the number of for which AAR has already been identified or is very likely to be diagnosed in a near future, as well as the number of structures that are under or planned for construction, which may also come to develop AAR is why it is still nowadays a major concern. Therefore, a study is being conducted at LNEC to diminish the negative impact of AAR by increasing knowledge on how to reliably control AAR in new structures and on how to properly assess its extent and potential for future development in the existing ones, so that the risks to structural integrity and need for mitigation/remediation actions can be properly assessed. This paper presents methodologies, based on state-of-the-art knowledge collected on that study, which may be used by the construction industry stakeholders in the prevention of AAR in new concrete structures and on AAR diagnosis and prognosis in existing concrete structures. The presented information also provides an insight to LNEC specifications that LNEC will soon publish on this thematic.